2014
DOI: 10.3390/molecules19068011
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabutylammonium Bromide (TBABr)-Based Deep Eutectic Solvents (DESs) and Their Physical Properties

Abstract: Density, viscosity and ionic conductivity data sets of deep eutectic solvents (DESs) formed by tetrabutylammonium bromide (TBABr) paired with ethlyene glycol, 1,3-propanediol, 1,5-pentanediol and glycerol hydrogen bond donors (HBDs) are reported. The properties of DES were measured at temperatures between 303 K and 333 K for HBD percentages of 66.7% to 90%. The effects of HBDs under different temperature and percentages are systematically analyzed. As expected, the measured density and viscosity of the studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 38 publications
7
75
0
1
Order By: Relevance
“…The experimental molar volumes of the DESs studied in this work are shown graphically as symbols in Figure 2. Values of molar volume occupied a wide range starting from 72 cm 3 /mol to 264 cm 3 …”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental molar volumes of the DESs studied in this work are shown graphically as symbols in Figure 2. Values of molar volume occupied a wide range starting from 72 cm 3 /mol to 264 cm 3 …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Deep eutectic solvents, when carefully designed for a particular application can replace conventional ionic liquids and be used economically in large industrial scales [1]. Many studies have focused on exploring the physico-chemical characteristics of these liquids [2][3][4][5]. These and many similar studies indicated that the physical and thermodynamic properties of the DES are profoundly affected by the nature of DES components, their composition, temperature, pH value and moisture and impurities content.…”
Section: Introductionmentioning
confidence: 99%
“…(2) and (3)), the NRTL model provided better calculation results (except the results of GLE at 343.2 K) since it used three adjustable parameters while the PR-EoS method used only one adjustable parameter. was obtained from the extrapolation of the viscosity of tetrabutylammonium bromide [39] and a further equation for different chains [22,23]. In that much (also see Fig.5c and Fig.5d M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t A c c e p t e d M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t 21 Table 3 p (MPa) 10 5 η 1 (Pa·s) 10 10 D 1 0 (m 2 /s) 10 predicted; points: experimental; •, this work from FMP; ▲, from Scurto et al [12].…”
Section: Experimental and Modeled Solubility Datamentioning
confidence: 99%
“…This is the reason that the alkyl chain length was longer, the polarity was lower, and the viscosity was higher, so the solubility of baicalin decreased [24]. Comparison among DES-1, DES-2, and DES-3 indicated that the extraction yield with DES-1 was maximal.…”
Section: Comparison Of the Extractability Of Dessmentioning
confidence: 99%